Fall 1999 Iowa field report, Chris Edwards - Edwards, Chriset al (1999)
An annotated list of birds sighted by Chris Edwards. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of fall 1999. Epson - sheet feed